ANALISIS YURIDIS KEABSAHAN PERJANJIAN KREDIT BANK OLEH NASABAH YANG DENGAN OBJEK HARTA BERSAMA DALAM PERKAWINAN - Nopiana Mozin (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
The discussion related to bank credit problems cannot be denied that there are urgent matters that can be considered disturbing for the bank as a creditor, one of which is related to the impact of divorce which certainly causes problems in terms of implementing the credit agreement system made. In several previous studies, it was found that after a divorce, customers face unfavorable financial conditions, so in the end they experience problem loans because the object of credit is joint property. Spouses who have divorced and are entitled to gono-gini property, often have disputes about this. However, the wishes of each party are usually contrary to the laws applicable to the divided gono-gini property. The purpose of this study is to analyze the juridical joint property with the marriage Agreement and analyze the validity of Bank Credit Agreements by customers who are bound by marital Status with the object of joint property.